P-82 IMPACT OF HEPATITIS C VIRUS ERADICATION WITH DIRECT ANTIVIRAL DRUGS ON GLYCEMIC CONTROL AFTER LIVER TRANSPLANTATION - Alicia Araújo de Oliveira; Samanta Teixeira Bastos; Claudia Cristina Tavares de Souza; Eduardo de Souza Martins Fernandes; Henrique Sérgio Moraes Coelho; Cristiane Villela-Nogueira; Nathalie Carvalho Leite (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Liver transplant patients have increased risk of type 2 diabetes (T2DM). Although hepatitis C virus (HCV) is an independent risk factor for insulin resistance and T2DM, there is no consensus on the impact of antiviral treatment on sustained glycemic control, particularly in liver transplant patients with HCV (HCV-LT). Objective: Evaluate the impact of viral HCV eradication with direct antiviral drugs on long term glycemic control of HCV-liver transplanted (HCV-LT) patients. Patients / Materials and Methods: A retrospective cohort of HCV-LT recipients with sustained virological response (SVR) after direct-antiviral treatment (DAA) was included in this longitudinal study. Clinical and laboratory data were collected before antiviral treatment and sequentially after SVR. A Cox Regression analysis was performed to evaluate the variables associated with glycated hemoglobin (A1C) on target (≤ 7% and ≤ 5.6% with and without T2DM) at the end of the follow-up period. Results and Discussion: Overall, 140 eligible HCV-LT patients were included (64% male, 63 ± 9 yrs, 15% with BMI ≥ 30 kg/m2, 64% with T2DM) and followed for 43 (19-70) months. After LT, 79% used tacrolimus, 34% Sirolimus and 14% prednisone. Before treatment 71% had A1C on target. At follow up this rate increased to 77%, with add-on insulin/increased doses in 14%, withdraw/reduced doses in 12% and diet/oral treatment in 76% of HCV-LT patients.On multivariate Cox analysis, A1C on target at follow-up were independently associated with diet/oral treatment (HR:2.77; 95%CI,1.33-5.78;p=0.006) and time between LT and end of DAA treatment (HR:0.996; 95%CI,0.992-1.000;p=0.045), adjusted for age, gender, weight gain and immunosuppressants. Conclusions: Over 70% of HCV-LT patients with SVR remained in good glycemic control over time, which was associated with initial and long-lasting non-insulin treatment. Of note, A1C on target was inversely associated with time from transplant to the end of DAA and subsequent HCV eradication, despite other important factors for long-term glycemic control.